RELATED ARTS AS A MEANS OF FORMATION PEDAGOGICAL CULTURE FUTURE MUSIC TEACHER - T.D. Sydorenko (Academy of Cognitive and Natural Sciences, 1999)
The present article deals with the guestion of formation of pedagogical culture of music teachers and the role of the interaction of different aspects of art in this process. Using the examples of life and activity of well-known figures of national culture such as G. Skovoroda, T. Shevchenko, M. Lysenko, Lesya Ukrainka etc. The author shows the importance and influence of the introduction of students with the contiguous aspects of art on the development and formation of broad-minded and of great erudition teachers to come.